Medication-related burden and associated factors among diabetes mellitus patients at Felege Hiwot Comprehensive Specialized Hospital in northwest Ethiopia - Bekalu, Abaynesh Fentahun; Yenit, Melaku Kindie; Tekile, Masho Tigabe; Birarra, Mequanent Kassa (Frontiers in Clinical Diabetes and Healthcare, 2022)
Background Evaluating the medicine burden from the patients’ perspective is essential for getting good health outcomes of diabetes mellitus (DM) management. However, data are limited regarding this sensitive area. Thus, the study was aimed to determine the medication-related burden (MRB) and associated factors among DM patients at Felege Hiwot Comprehensive Specialized Hospital (FHCSH) in northwest Ethiopia. Methods A cross-sectional study was conducted on 423 systematically selected DM patients attending the DM clinic of FHCSH from June to August 2020. The medication-related burden was measured by using the Living with Medicines Questionnaire version 3 (LMQ-3). Multiple linear regression was used to identify factors associated with medication-related burden and reported with 95% confidence interval (CI). p-value <0.05 was considered as statistically significant to declare an association. Results The mean LMQ-3 score was 126.52 ( ± 17.39). The majority of the participants experienced moderate (58.9%, 95% CI: 53.9–63.7) to high (26.2%, 95% CI: 22.5–30.0) degrees of medication burden. Nearly half (44.9%, 95% CI: 39.9–49.7) of the participants were non-adherent to their prescribed medications. VAS score (B = 12.773, p = 0.001), ARMS score (B = 8.505, p = 0.001), and fasting blood glucose (FBS) on visit (B = 5.858, p = 0.003) were significantly associated with high medication-related burden. Conclusion A significant number of patients suffered from high medication-related burden and non-adherence to long-term medicine. Therefore, multidimensional intervention to decrease MRB and to upgrade adherence is required to increase patients’ quality of life.